New bushcrickets of the tribe Meconematini (Orthoptera, Tettigoniidae, Meconematinae) from China - Shi, Fu-Ming; Bian, Xun; Chang, Yan-Lin (Zootaxa, 2011)
Two new genera and two new species of meconematine tettigoniids are described from China, i.e. Sinodecma Shi, Bian & Chang gen. nov., Shoveliteratura Shi, Bian & Chang gen. nov., Sinodecma acuta Shi, Bian & Chang sp. nov. and Shoveliteratura triangula Shi, Bian & Chang sp. nov.. The type specimens are kept in the Museum of Hebei University.